Composites of recycled oxo-biodegradable foils filled with wood flour - Ryszkowska, J.; Sałasińska, K. (Polimery, 2010)
Wood-polymer composites (WPC) have been derived on the basis of oxo-biodegradable polyethylene (PE-HD) from recycling containing 1 % d2w and wood flour with stable parameters up to the amount of 32 wt. %. The properties of the obtained composites were characterized according to EU standard procedures regarding polymer-wood composites. The density, moisture content, combustion heat, flammability (Table 2, Figs. 3, 5-7), resistance to accelerated ageing (Table 1, Fig. 4) and mechanical properties were determined. The analysis were performed for the purpose of determining whether the obtained WPC materials obtained from oxo-biodegradable polymers and wood possess the properties making them suitable for further applications as alternatives for traditional virgin polymers.